Utility of ultrasonography in guiding modification of disease modifying anti‐rheumatic drugs and steroid therapy for inflammatory arthritis in routine clinical practice. (19th August 2016) - Tan, York Kiat; Chew, Li‐Ching; Allen, John C; Lye, Weng Kit; Htay, Lei Lei; Hassan, Ali; Conaghan, Philip G; Thumboo, Julian
Abstract: Objective: To determine the utility of ultrasonography in guiding modification of disease‐modifying anti‐rheumatic drug (DMARD) and steroid therapy for inflammatory arthritis (IA) in routine clinical practice. Methods: In this retrospective study, we analyzed DMARD and steroid use in IA patients referred to a rheumatologist‐led ultrasound clinic. Power Doppler (PD) vascularity and greyscale (GS) synovial hypertrophy joint findings were categorized as positive/negative for each patient. The erythrocyte sedimentation rate (ESR) was used as a measure of disease activity. Results: We assessed single visit data for 46 adult IA patients: 67.4% ( n = 31) rheumatoid arthritis (RA), 15.2% ( n = 7) psoriatic arthritis, 10.9% ( n = 5) spondyloarthritis, and 6.5% ( n = 3) undifferentiated IA. The mean ESR was 28.8 mm/h. Thirty‐seven patients with both GS and PD ultrasound results were subsequently analyzed. All patients ( n = 10) escalated and/or initiated on DMARD and 9/10 patients escalated or initiated on steroids were PD and GS positive. Six of seven patients with dose reduction and/or cessation of DMARDs and five of seven patients with dose reduction or cessation of steroids were PD negative. Of six patients who were GS positive and PD negative, three had dose reduction and/or cessation of DMARDs, while four had dose reduction of steroids; none of the six patients had DMARD/steroid escalation. Conclusion: By clarifying joint inflammation in an IA cohort with overall low ESR, ultrasonography of physician‐selected joints can improve clinical assessment, resulting in treatment modification. Positive PD findings were particularly influential, while the clinical significance of GS positivity alone requires further investigation.